ETIOLOGICAL FACTORS LEADING TO PURULENT MEDIASTINITIS - A.O. Okhunov; K.Kh. Boboev (Scholar Express Journals, 2023)
This review article provides information on the causes of primary mediastinitis. Back in the 19th century, surgeons identified two ways of infection penetration into the mediastinum: from the esophagus during its perforation and from the cellular spaces of the neck. This corresponds to the division of mediastinitis into primary and secondary. Primary purulent mediastinitis is considered if it develops as a primary purulent complication of diseases and injuries of the mediastinal organs. Secondary purulent mediastinitis develops with contact or metastatic spread to the mediastinum of the purulent process, in the presence of a primary purulent focus outside the mediastinal tissue. From a clinical point of view, it seems appropriate to allocate a special group - postoperative mediastinitis. It is concluded that the relevance of primary mediastinitis is preserved and knowledge in this field of surgery is still in demand.
Keywords: purulent mediastinitis; esophageal damage; computed tomography in mediastinitis; surgical infection